A comparison study between endoscope‐assisted and the standard approach in the harvesting of the free rectus femoris muscle flap. Issue 1 (28th December 2017) - Lee, Jiunn‐Tat; Hsu, Honda; Lin, Chih‐Ming; Huang, Chieh‐Chi; Chien, Sou‐Hsin
Abstract : Background: Endoscopic harvesting of muscle flaps is well described for gracilis, latissimus dorsi, gastrocnemius, and pectoralis major amongst others. So far there has been no description of endoscopic harvesting of the rectus femoris muscle as a free flap. The purpose of this study was to compare the perioperative outcomes of harvesting the free rectus femoris muscle flap endoscopically as compared to the standard approach. Methods: Fifty patients with lower limb defects reconstructed with free rectus femoris muscle flap between January 2014 and December 2016 were included in this study. Their ages ranged from 37 years old to 92 years old. The flaps were harvested with both the standard and endoscopical method. Comparative data between the two methods collected included: age, gender, comorbid illnesses, flap size, defect size, reconstruction time, and flap survival rate Results: Twenty patients underwent flap harvesting endoscopically and 30 were harvested with the standard technique. Their mean ages were 67 ± 9.4 and 65 ± 14 years old respectively ( P = .47). The defect size was 96 ± 60 cm 2 versus 81 ± 74 cm 2 ( P = .45). The flap size was 72 ± 34 cm 2 in the endoscopic group and 60 ± 42 cm 2 in the standard group ( P = .52). The mean total reconstruction time in the endoscopic group was 228 ± 48 minutes and 216 ± 64 minutes in the standard group ( P = .50). There was no significant difference between flap survival ( P = N/A), complication rates ( P = .33), and length of admission ( P = .84) in the two groups. Conclusion: Endoscope‐assisted harvesting of a free rectus femoris muscle flap is a feasible option and permits a small scar at the donor site.